Pengaruh Kualitas Sistem Informasi Digital dan Kualitas Jasa Pelayanan terhadap Kepuasan Nasabah Guru PNS SMP Kecamatan Wado - Vynka Nur Fadilla; Elly Halimatusadiah (Bandung Conference Series: Accountancy, 2023)
Abstract. Banks are financial institutions that are important in the life of the Indonesian people, not only to save and apply for credit but to serve the public's needs for financial transactions. As technology develops, financial services are no longer face-to-face but digital banking services such as BJB Digi banks are trying to improve the quality of service to customers directly so that customers feel comfortable and satisfied. Some factors affect customer satisfaction including the quality of digital information systems and the quality of service. Problems with BJB Digi ShopeePay balances not arriving within a few hours and the attitude of the security guard is not friendly, lack of courtesy to parents. The purpose of this study was to find out how much influence the quality of digital information systems and service quality have on customer satisfaction for PNS Teachers at SMP Negeri Wado District. The research method used is descriptive and verification methods with a quantitative approach. The data collection technique used the Google form questionnaire, the study population was BJB customers in Wado District using a digital information system using a purposive sampling technique, a sample of 65 respondents were BJB Teachers, PNS SMP customers. Instrument test results data are all valid and reliable. The results showed that at a significant level of 5% the quality of digital information systems and the quality of services had a significant positive effect on the satisfaction of PNS Teacher satisfaction at SMP Wado District. Abstrak. Bank merupakan lembaga keuangan yang penting dalam kehidupan masyarakat Indonesia, bukan hanya menabung dan mengajukan kredit, tetapi untuk melayani kebutuhan masyarakat terhadap transaksi keuangan. Seiring perkembangan teknologi, layanan keuangan tidak lagi hanya secara tatap muka tetapi dilakukan layanan perbankan secara digital seperti BJB Digi, bank berupaya meningkatkan kualitas pelayanan kepada nasabah secara langsung agar nasabah merasa nyaman dan puas. Terdapat faktor yang mempengaruhi kepuasan nasabah diantaranya kualitas sistem informasi digital dan kualitas jasa pelayanan. Permasalahan pada BJB Digi saldo ShopeePay tidak masuk dalam beberapa jam dan attitude dari satpam tidak ramah, kurangnya sopan santun kepada orangtua. Tujuan penelitian ini untuk mengetahui seberapa besar pengaruh kualitas sistem informasi digital dan kualitas jasa pelayanan mempengaruhi kepuasan nasabah Guru PNS SMP Kecamatan Wado. Metode penelitian yang digunakan metode deskriptif dan verifikatif dengan pendekatan kuantitatif. Angket atau kuesioner G-Form merupakan dipilih buat pengumpulan data, nasabah BJB Kecamatan Wado memakai sistem informasi digital bagai populasi mengenakan teknik purposive sampling sampel 65 orang Guru PNS SMP. Hasil uji instrumen data semua benar dan reliabel. Hasil penelitian menunjukkan bahwa pada tingkat signifikan 5% kualitas sistem informasi digital dan kualitas jasa pelayanan berpengaruh positif signifikan terhadap kepuasan nasabah Guru PNS SMP Kecamatan Wado.